RATIONALE FOR POPULARIZATION OF PROCESSING OF POLYMER WASTE FROM TIRES IN INDUSTRY - Паладийчук, Юрий; Телятник, Инна (Modern engineering and innovative technologies, 2022)
The rubber and plastics industry is increasingly becoming an important industry. Polymers are used in almost all areas of material production and non-productive sphere. Demand for finished products made of polymeric materials from the most important consu